Gambaran Faktor Perilaku COVID-19 pada Mahasiswa di Universitas Cenderawasih Kota Jayapura Provinsi Papua - Rindi Maylia Faramita; Henry Setyawan Susanto; Dwi Sutiningsih; Mohammad Arie Wurjanto (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: The rate of COVID-19 cases is still high in Jayapura City to date in one day it can contribute 30 to 35 positive patients. The form of prevention behavior in students has not been optimally implemented. the addition of positive cases every day can be triggered due to the lack of information related to the corona virus. The purpose of this study was to describe the behavioral factors to prevent COVID-19 in students.Methods: The population in this study were students of Cenderawasih University, Jayapura City. The study was conducted in January – February 2021 on 100 subjects selected by purposive sampling technique. Subjects were measured using an online questionnaire containing questions and statements regarding research variables such as knowledge, attitudes, practices, sources of information, social support and support from health workers. Data were analyzed by univariate analysis and bivariate analysis.Result: The results showed that 67% of students' level of knowledge about the causes, symptoms, modes of transmission and forms of prevention of COVID-19 was good, 58% of students' attitudes were quite good in seeking information and understanding forms of the spread of COVID-19 and 53% of students' practice levels in prevention. COVID-19 is good, with 49% of students getting information through social media, 100% of students getting social support, and 45% getting support from health workers.Conclusion : Students have received social support and support from health workers in preventing COVID-19. the majority of students have good knowledge but there are still students with less than optimal attitudes and practices.